2021
DOI: 10.1007/s00168-021-01069-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic shocks and their effect on the schooling and labor participation of youth: evidence from the metal mining price boom in Chilean counties

Abstract: We analyze the effect of an exogenous economic shock on youth, specifically their incentive for preferring to participate in the labor market over continuing their education. We examine the Chilean case and the sustained increase in the market price of the minerals extracted there during the period of Metal Mining Price Boom between the years 2003 and 2011. Chile is a large-scale producer of metals, being the world's largest producer of copper and the third largest producer of molybdenum. The prices of such me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…In particular, the authors show that during the recent commodity price boom, enrollment rates of people aged 17-20 decrease in municipalities with high local labor market exposure to this sector while employment rates increase for the same cohort. Similarly, Trujillo and Puello (2021) show that this commodity price boom led to lower returns to schooling, decreasing municipalitylevel enrollment rates of young individuals (aged 15-24), and increasing their labor market participation.…”
Section: Mining In Chilementioning
confidence: 93%
“…In particular, the authors show that during the recent commodity price boom, enrollment rates of people aged 17-20 decrease in municipalities with high local labor market exposure to this sector while employment rates increase for the same cohort. Similarly, Trujillo and Puello (2021) show that this commodity price boom led to lower returns to schooling, decreasing municipalitylevel enrollment rates of young individuals (aged 15-24), and increasing their labor market participation.…”
Section: Mining In Chilementioning
confidence: 93%
“…To date, empirical literature that analyzes the impacts of exogenous economic shocks has mostly focused on the opportunity costs between schooling and participating in the labor market, and typically within the context of economic crisis (Goldin, 1999;Schady, 2004;Pérez-Trujillo and Rodríguez-Puello, 2021). The results of these studies are ambiguous.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The salary boom also had an impact in terms of its distribution between skilled and unskilled workers in the areas more exposed to the shock (Pérez-Trujillo and Rodríguez-Puello, 2021). Pellandra (2015), who analyzes the impact of the MMPSC shock on local wages and employment levels for the Chilean provinces during the expansion phase (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) found that those provinces more exposed to the shock experienced an increase in the wages of low-skilled workers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations